Design of forest and land fire complaint system in BPBD Tebo Jambi regency - Muhammad Fauzan; Dwi Agus Diartono (Institute of Computer Science (IOCS), 2023)
A good and responsive service quality is a requirement for the success of regional disaster management agencies such as forest and land fires, but of course information technology is needed that is able to support performance and optimize the information obtained in the complaint process at BPBD Tebo Regency, Jambi province. Therefore the author aims to find solutions to problems that exist in BPBD Tebo Regency by designing an information system website that helps process complaints that are still done manually and are less efficient so that they are more advanced, accurate and facilitate the complaint process. This complaint information system provides convenience and helps the complaint process to be easier, more efficient and structured. This complaint information system is a website-based system, using the PHP programming language with the Laravel framework method and using the Mysql database to make it easier to create a design website for complaints of forest and land fires at BPBD Tebo district.